Peranan Sistem Informasi Komputer Dalam Evolusi Bisnis Ke Era Digital 5.0 - Abdul Sakti (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
The development of information technology has significantly impacted the evolution of business into the digital era 5.0. In this context, the role of Computer Information Systems (CIS) becomes crucial in facing the challenges and opportunities that arise. This study aims to explore the role of CIS in Business 5.0, focusing on technology integration and business processes, analytical capabilities and data-driven decision-making, automation and operational efficiency, information security and compliance, as well as accountability and transparency. The research methodology involved literature search from academic databases and scientific journals using relevant keywords such as "digital transformation," "Business 5.0," "Computer Information Systems," and "technology integration." Selected information sources were then filtered based on inclusion and exclusion criteria, such as relevance, source credibility, and publication year. The results of literature analysis indicate that technology integration and business process serve as the foundation for the role of CIS in Business 5.0. Analytical capabilities and data-driven decision-making, along with automation and operational efficiency, also significantly contribute to increased productivity and organizational innovation. Additionally, aspects of information security and compliance, together with accountability and transparency, are key to building trust among stakeholders. The discussion of the results highlights the importance of understanding and implementing these concepts in the context of Business 5.0. By considering technology integration and business processes, analytical capabilities and data-driven decision-making, automation and operational efficiency, information security and compliance, as well as accountability and transparency, companies can optimize the role of CIS in transforming their businesses into the digital era 5.0, enhancing competitiveness, and achieving long-term success.